PENGARUH PROMOSI, KUALITAS, DAN PACKAGING TERHADAP MINAT PEMBELIAN MIE LETHEK KULINER KHAS BANTUL - Nur Wahyuni (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2022)
Yogyakarta is one of Indonesia's various regions with diversity, uniqueness, and excellence, especially in the culinary field. One of the areas with its distinctive culinary is Bantul with